Sistem Informasi Administrasi Surat Masuk Dan Surat Keluar Pada Biro Rektorat Universitas Katolik Santo Thomas Medan - Saragih, Fera Nita Yousida; Damanik, Romanus (LPPM UNIKA Santo Thomas Medan, 2018)
Processing incoming data and outgoing letters at the rector's bureau at Santo Thomas Catholic University in North Sumatra has been using storage of accumulated data, in the form of sheets of paper, then the search requires a long process, because it has to turn back the ledger, so the letter will hard to find, and damage if the letter has been stored for a long time in the mail storage cabinet. Data storage of incoming letters, dispositions and outgoing letters has used the database so that it further accelerates the workings of the Rector's Bureau, because incoming mail and outgoing mail data do not need to be recorded or written into a letter book.